Measurement of Solubility of CO2 in NaCl, CaCl2, MgCl2 and MgCl2 + CaCl2 Brines at Temperatures from 298 to 373 K and Pressures up to 20 MPa Using the Potentiometric Titration Method - Bo Liu (MDPI AG, 2021)
Understanding the carbon dioxide (CO2) solubility in formation brines is of great importance to several industrial applications, including CO2 sequestration and some CO2 capture technologies, as well as CO2-based enhanced hydrocarbon recovery methods. Despite years of study, there are few literature data on CO2 solubility for the low salinity range. Thus, in this study, the solubility of CO2 in distilled water and aqueous ionic solutions of NaCl, MgCl2, CaCl2 and MgCl2 + CaCl2 were obtained in a low salinity range (0–15,000 ppm) at temperatures from 298–373 K and pressures up to 20 MPa using an accurate and unconventional method called potentiometric titration. An experimental data set of 553 data points was collected using this method. The results of the experiments demonstrate that increasing pressure increases the solubility of CO2 in various brines, whereas increasing temperature and salinity reduces the solubility. The role of different ions in changing the solubility is elaborated through a detailed discussion on the salting-out effect of different ionic solutions. To verify the experimental results of this research, the solubility points obtained by the potentiometric titration method were compared to some of the well-established experimental and analytical data from the literature and a very good agreement with those was obtained.